Practicing Catholic : ritual, body, and contestation in Catholic faith - Morrill, Bruce T.; Ziegler, Joanna E.; Rodgers, Susan, 1949- (Palgrave Macmillan, 2006)
This collection explores Catholicism as a faith grounded in ritual practices. Ritual, encompassing not only the central celebration of Mass but popular ceremonies and devotional acts, comprises a base for Catholicism that requires both constant engagement of the human body and negotiation of various types of power, both human and divine. Practicing Catholic brings together top scholars from various backgrounds to explore methodologies for studying ritual and Catholicism. Scholars focus their essays on particular aspects of ritual within Catholic practice. The collection is divided into six easy-to-follow sections: Performance, Liturgy, and Ritual Practice, Catholic Ritual in History, Contemporary Ritual Practices of Healing, Catholic Ritual as Political Practice, Contemporary Mass Media as a Domain for Catholic Ritual Practice, and a final section drawing them together.